Comprehensive multi-omics analysis reveals prognostic, immune, and therapeutic signatures of TNFAIP family genes in breast cancer - Tahereh Barati; Madiheh Mazaheri Moghaddam; Fatemeh Mokhles; Zohreh Mirzaei; Amir Ebrahimi; Golsa Nayeb Ghanbar Hosseini; Najaf Allahyari Fard (PLoS ONE, 2026)
Background Tumor necrosis factor-alpha-induced proteins (TNFAIPs) are key regulators of inflammation, apoptosis, and immune signaling, yet their integrated roles in breast cancer (BC) remain poorly characterized. While individual TNFAIP members have been studied in other cancers, a comprehensive multi-omics characterization of this gene family in BC is still needed. Methods We performed an integrative bioinformatics analysis using public datasets (UALCAN, TIMER, bc-GenExMiner, cBioPortal, STRING, GeneMANIA, Enrichr, MethSurv, GDSC, CTRP, and HPA) to evaluate TNFAIP family members in BC. Expression, genomic alterations, methylation patterns, immune infiltration, and drug sensitivity were analyzed across clinical and molecular subtypes. Where applicable, multiple hypothesis testing was controlled using the Benjamini–Hochberg false discovery rate (FDR) method. Results Among TNFAIPs, TNFAIP6 and EFNA1 were significantly upregulated in BC, while TNFAIP1, TNFAIP2, TNFAIP3, PTX3, TNFAIP8, and STEAP4 were downregulated. Elevated TNFAIP2, TNFAIP3, and TNFAIP8 expression correlated with improved overall survival (OS). Multi-database integration revealed that TNFAIP3 expression was strongly correlated with infiltration of CD4 ⁺ T cells, dendritic cells, and neutrophils. Functional enrichment highlighted the NF-κB, PI3K-Akt, and TNF signaling pathways as key regulatory axes. Drug-sensitivity analyses indicated subtype-dependent responses linked to TNFAIP dysregulation. Conclusion This study provides a comprehensive multi-omics characterization of TNFAIP family genes in BC, addressing the role of inflammatory signaling in tumor progression and identifying potential biomarkers and therapeutic targets. These findings enhance the understanding of TNFAIP-mediated molecular networks and offer a resource for translational and experimental research in BC.